Assessing the impact of global change on flood dynamics and rice submergence susceptibility in the Kilombero floodplain, Tanzania - Tuschen, Mark; Steinbach, Stefanie; Sin, Hnin Phyu; Evers, Mariele (Frontiers in Earth Science, 2025)
Climate and land use change are increasingly altering the water balance and flood dynamics of East African wetlands. In Tanzania’s Kilombero floodplain, rice cultivation relies on seasonal flooding, which is becoming more variable and intense due to climate and land use change. While floodwater is essential for rice cultivation, prolonged submergence poses a threat to yields and regional food security. However, it remains unclear how catchment-scale hydrological changes translate into floodplain-scale flood dynamics and submergence risks for rice crops. To address this, we developed a HEC-RAS 2D hydrodynamic model of the Kilombero floodplain, simulating future flood dynamics under climate change (RCP 4.5 and 8.5) and land use change scenarios. We assessed the susceptibility of rice crops to prolonged submergence by integrating flood model outputs with physiological traits of rice plants. Results show that high-emission scenarios (RCP 8.5) and extensive land conversion to rice cultivation in the floodplain significantly increase areas prone to prolonged rice crop submergence compared to baseline conditions and moderate-emission scenarios (RCP 4.5). Rice plant height was the dominant factor influencing submergence susceptibility. Our findings highlight the importance of integrating hydrodynamic modelling with crop characteristics to inform adaptive rice variety selection and agricultural planning in the context of global change.